Improving Students' Mathematics Learning Outcomes by Using Quizzi - Krisantus N Kantur; Edy M Priyono; Nurul Hikmah; Asyifa Aulia Zahro; Andy Ahmad; Ageng Triyono (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study aims to improve the mathematics learning outcomes of fourth-grade students at MI Sirojul Athfal on mixed integer operations through the application of Quizzi learning media. This study uses a qualitative approach with the Classroom Action Research (CAR) method which is implemented in two cycles. The research subjects consisted of fourth-grade students with data collection techniques through interviews with teachers, distributing questionnaires to four students, observing the learning process, and documentation. The results of the study indicate that students experience various difficulties in learning mathematics, including negative perceptions of mathematics as a difficult subject, low learning motivation, obstacles in group work, lack of self-confidence, minimal interest in learning, and weak understanding of basic concepts. The application of Quizzi media in the learning process has been proven to be able to increase student engagement and enthusiasm. This has an impact on significant improvements in learning outcomes in each cycle. In the second cycle, the level of student learning completion has reached 80%, so the study was stopped because it has met the established success indicators. Thus, it can be concluded that the use of Quizzi media is effective in improving student learning outcomes on mixed integer operations. This study provides implications that the use of interactive learning media can be an alternative innovative strategy in improving the quality of mathematics learning in elementary schools.